Procesos de atención de enfermería en pacientes con insuficiencia renal que acuden al Centro de Diálisis Dial Ríos del Cantón Babahoyo, Provincia de Los Ríos periodo octubre 2019 - marzo 2020. - Campuzano Amat, Cindy Tatiana (2020)
The present research study whose theme is NURSING CARE PROCESSES IN PATIENTS WITH RENAL INSUFFICIENCY THAT COME TO THE RÍOS DEL CANTÓN DIALYSIS CENTER BABAHOYO, PROVINCE OF LOS RÍOS PERIOD OCTOBER 2019 - MARCH 2020 had the general objective of determining the application of the nursing care process in patients with renal insufficiency who attend the Dial Ríos dialysis center of the Babahoyo canton, province of Los Ríos, period October 2019 - March 2020. For such purposes, a data collection will be carried out based on the aspects studied in a population of 183 patients who attended the Dial Ríos center in the indicated period, applying a sampling formula it was determined that the sample is 164 patients and was performed an interview was conducted with the nursing professionals of the Center under study. As significant results we have 69%, it does not evaluate and does not keep track of its intervention, limiting in its work according to processes estimated by 75% of nurses, in addition educational talks on signs and symptoms in infection are required for users. A proposal was made with the objective of improving the level of knowledge of nursing staff in the management of the PAE nursing care process, to provide good care for patients with chronic renal failure treated in Dial Ríos.